In House Training Gerakan Literasi Sekolah Bagi Guru di Sekolah - Azizah, Amalia Nurul; Kurniawan, Alfi Muklis (Communautaire: Journal of Community Service, 2023)
The literacy movement in schools aims to develop student's character through cultivating various kinds of literacy, manifested in the school literacy movement so that it becomes lifelong learning. Community service is carried out by providing socialization in the form of in-house training in forming a culture of elementary school literacy for teachers at SD Negeri Karanglo to become a discourse in the development of science and education regarding the implementation of the school literacy movement. Activities using lecture methods, question and answer, discussion and practice. The implementation of community service, in general, can be successful in terms of participant participation, considering that of the ten target participants who were invited, ten people attended as well. The participants felt that this service activity was very beneficial because, as educators, they felt the need to develop skills and foster a literacy culture in elementary schools.